Perancangan Aplikasi Sistem Pakar Diagnosa Awal Kanker Reproduksi Wanita Dengan Metode Certainty Factor - Sukmawati Anggraeni Putri; Elin Panca Saputra (STMIK Budi Darma, 2018)
Until now, cancer is one that suffered by the people of Indonesia, especially in cervical cancer (cervix) suffered by Indonesian women. Not only cervical cancer suffered by Indonesian women, but also other diseases that attack the female reproductive organs. Such diseases, cervical cancer, ovarian cancer, endometrial cancer, vaginal cancer, ovarian cysts and myomas. To prevent the number of deaths of patients, of course the initial diagnosis as one of the solutions. As used in this study in development an early diagnosis system of female reproductive cancer. This expert system adds value to the technology to assist in the handling of an increasingly sophisticated information age. This Expert System Application generates an Update that enables patients who suffer from symptoms that are felt by the patient. This system is also a result of the necessity of women suffering from cancer experienced by patients. The amount of trust value is the result of calculation using Certainty Factor method.